(Tele)Work and Care during Lockdown: Labour and Socio-Familial Restructuring in Times of COVID-19 - Iduzki Soubelet-Fagoaga (MDPI AG, 2021)
COVID-19, and the lockdown requirement, altered our daily lives, including the restructuring of work and socio-familial organisation of millions of people. Through two studies, we explored how workers experienced this period. The first, qualitative study (N = 30) aimed to understand how workers lived through lockdown by identifying the key elements that shaped their experiences. Thematic content analysis revealed four emerging themes: (1) work and socio-health situation in which lockdown was experienced; (2) consequences on work organisation and resources available for change; (3) work–life balance management; and (4) psychosocial consequences and coping with the situation. The second, quantitative study (N = 332) explored the socio-health situation, new work organisation, work–life balance, and psychosocial consequences and coping strategies developed during this period, analysing participants’ differences in terms of gender, working modality (on-site or teleworking) and care responsibilities through ANOVA analysis. Results revealed the non-democratic nature of the pandemic, with differences and similarities according to gender, working modality and having or not having dependents. Results are discussed identifying areas that need to be addressed to ensure the well-being of workers.